KEWENANGAN PRESIDEN, DPR DAN DPD DALAM PEMBENTUKAN UNDANGUNDANG DI REPUBLIK INDONESIA - Deni Syaputra (Menara Ilmu, 2018)
The amendment of the 1945 Constitution, has reversed the power of formulating the law, whichwas originally in the hands of the President, became a House of Representatives power. But everylaw-making, whether coming from the House of Representatives and from the President, isobliged to come together for joint approval. Without the consent of both parties, the drafting ofthe law can not be passed into law. From the beginning the 1945 Constitution did not apply TriasPolitica Montisquie in matters governing the legislative authority, although the DPD maypropose the bill in certain fields. In every country every legislation is always discussed jointly byParliament and Government, because it is the Government that will implement the law, then thegovernment is also discussing together with the parliament to obtain mutual consent. Uponmutual consent, any such drafting of the law shall be approved by the President.Keywords: Authority, Establishment, Law